The Dilemma of Scale: competing imperatives for global restoration - Sigman, E. (Wiley, 2021)
Social–ecological restoration (SoER) embraces the nested interdependence of societies and ecosystems. An outpouring of SoER research has substantively shaped the global restoration agenda and will continue to play a critical role as the UN Decade on Ecosystem Restoration unfolds. In this article, I argue that global restoration ambitions are limited by two competing imperatives in SoER literature. The first imperative seeks to generalize restoration standards and metrics through rapid coordination and scaling. The second imperative seeks to upend problematic power dynamics, demanding social inclusivity and site specificity at levels that tend to resist scaling. Although these imperatives do not necessarily compete in theory, they often do in practice. Relying on a synthesis of key articles and expanding on the concept of “social-ecological mismatches” (Cumming et al. 2006), I examine how the prevailing SoER research discourse creates a confounding landscape for restoration practitioners, who face what I term the “Dilemma of Scale.” I explore how this dilemma perpetuates systems of global inequality and inhibits efforts to effectively animate initiatives like the UN Decade on Ecosystem Restoration. I suggest that the Dilemma of Scale can be effectively mitigated by (1) identifying values that span both imperatives and work to decouple SoER projects from systems of exploitation and oppression and (2) expressly incorporating historical methods into SoER research and projects.